Prospects and Challenges In Developing ’Japanese Studies’ Program in Bangladesh: Lessons From the University of Dhaka - Akon, Md. Saifullah; Sharmin, Dilruba (WILAYAH: The International Journal of East Asian Studies, 2020)
Abstract: Japanese Studies has entered a booming period in Bangladesh where the growing demand for knowledge on Japan, particularly Japanese development experience, society, and culture, has intensified. Besides, the increasing number of Japanese companies and opportunities to work in Japan so far is conducive to the increasing number of students in the Japanese language. Considering the given facts, academic institutions of Bangladesh need to initiate ’Japanese Studies’ programs to produce ’Japanologists’-contextual and transitional expertise. The larger goal of this study is to identify the major prospects and challenges and consider the future directions for the Japanese Studies program. The paper intends to think alternatively beyond the ’ivory tower’ mindset of a large number of Bangladeshi students as well as academicians and show the prospects of Japanese Studies with sustainable employment opportunities through industry-academia collaboration. The methods and equipping tools employed in this paper include lexical scrutiny and contextual analysis under the qualitative research method to analyse the current state of knowledge and pedagogical development. Presenting the number of stumbling blocks of the Japanese Studies program in Bangladesh, the paper finally demonstrates the program’s future as an academic discipline. It ends with possible suggestions towards success in producing Japanologists to strengthen Bangladesh-Japan bilateral relations.